Inhibition of mPFC norepinephrine improved chronic post-thoracotomy pain in adult rats - Fan Zhang; Weicheng Qiu; Wenxiang Qing; Jin Li; Huan Chang; Rili Yu; Yanjun Zhou; Qin Liao (Annals of Medicine)
Background Chronic post-thoracotomy pain (CPTP) is characterized by high incidence, long duration, and severity of pain. Medial prefrontal cortex (mPFC) is a brain region closely associated with chronic pain, and norepinephrine is involved in pain regulation. But the role of mPFC norepinephrine in CPTP and its possible mechanism is unclear.Materials and methods Adult Sprague-Dawley (SD) male rats underwent sham or thoracotomy, and were microinjected with pAAV.Syn.shDβH.eGFP(AAV2/9) or vehicle into contralateral mPFC on the 3rd day after thoracotomy. The pain of rats was evaluated by mechanical withdrawal threshold and cold pain threshold around thoracotomy incision. Norepinephrine in mPFC microdialysates were determined by high performance liquid chromatography with electrochemical detection (HPLC-ECD). The mPFC was collected to assess norepinephrine synthase (dopamine beta-hydroxylase, DβH) and metabolic enzyme (monoamine oxidase A/B, MAO-A/B and catechol-O-methyltransferase, COMT), bradykinin, bradykinin receptor 2 (Bdkrb2), neuroinflammation (Iba1, IL-6 and TNF-α), Aquaporin-4 (AQP4) and IL-33.Results Right thoracotomy reduced the mechanical withdrawal threshold and cold pain threshold around incision, the expression of AQP4 and IL-33, increased norepinephrine, DβH, bradykinin, Bdkrb2, Iba1 and IL-6, but had no impact on MAO-A, MAO-B, COMT and TNF-α in contralateral mPFC. Inhibition of norepinephrine in contralateral mPFC increased the mechanical withdrawal threshold and cold pain threshold, the expression of AQP4 and IL-33, reduced norepinephrine, DβH, Bdkrb2, Iba1 and TNF-α, but had no significant effect on bradykinin and IL-6 in contralateral mPFC after right thoracotomy.Conclusions Inhibition of norepinephrine in contralateral mPFC after thoracotomy improved CPTP. The potential mechanisms may include rescuing the expression of AQP4 and IL-33, as well as reducing neuroinflammation and Bdkrb2 expression.